An ELISA-based assay for determining haemagglutinin potency in egg, cell, or recombinant protein derived influenza vaccines - Bodle, Jesse; Vandenberg, Kirsten; Laurie, Karen; Barr, Ian G.; Zhang, Ying; Rockman, Steven (Frontiers in Immunology, 2023)
Background: The current compendial assay for haemagglutinin antigen potency in influenza vaccine is the single radial immunodiffusion (SRID) which is time consuming and can lead to delays in release of vaccine. We previously described an alternate capture and detection enzyme linked immunoassay (EIA) that utilizes sub-type specific, sub-clade cross-reactive monoclonal antibodies (mAbs) that are haemagglutination inhibiting (HAI) and correlate with SRID. The aim of this study is to determine the applicability of EIA across current platforms for quantitation of seasonal quadrivalent vaccine. Methods: A single mAb capture and detection EIA was employed to quantitate hemagglutinin (HA) derived from different vaccine platforms and host organisms and compared to SRID and a polyclonal antibody based EIA. Results: We selected mAbs that displayed appropriate characteristics for a stability indicating potency assay which reacted to avian, insect and mammalian derived HA. Qualification of the homologous mAb assay against egg and cell derived HA demonstrated performance similar to that of the SRID however, superiority in sensitivity and specificity against strains from both influenza B/Victoria and B/Yamagata lineages. Analysis of drifted strains across multiple seasons demonstrated continued utility of this approach, reducing the need to develop reagents each season. With modification of the assay we were able to accurately measure HA from different platforms and process stages using a single calibrated reference standard. We demonstrated the accuracy of EIA when testing vaccine formulations containing selected adjuvants at standard and higher concentration. Accelerated stability analysis indicated a strong correlation in the rate of degradation between the homologous mAb EIA and SRID but not with EIA utilizing polyclonal antisera. Further, we demonstrated specificity was restricted to the trimeric and oligomeric forms of HA but not monomeric HA. Conclusion: We believe this homologous mAb EIA is a suitable replacement for the SRID compendial assay for HA antigen quantitation and stability assessment. Identification of suitable mAbs that are applicable across multiple vaccine platforms with extended sub-type reactivity across a number of influenza seasons, indicates that this assay has broad applicability, leading to earlier availability of seasonal and pandemic vaccines without frequent replacement of polyclonal antisera that is required with SRID.